2016
DOI: 10.1038/ncb3328
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NBR2 engages a metabolic checkpoint by regulating AMPK under energy stress

Abstract: Long noncoding RNAs (lncRNAs) have emerged as critical regulators in various cellular processes. However, the potential involvement of lncRNAs in kinase signaling remains largely unknown. AMP-activated protein kinase (AMPK) acts as a critical sensor of cellular energy status. Here we show that lncRNA NBR2 (neighbor of BRCA1 gene 2) is induced by the LKB1-AMPK pathway under energy stress. Upon energy stress, NBR2 in turn interacts with AMPK and promotes AMPK kinase activity, thus forming a feed-forward loop to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
227
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 254 publications
(239 citation statements)
references
References 43 publications
9
227
1
2
Order By: Relevance
“…Since many lncRNAs function to regulate the transcription of neighboring genes, the hypothesis that NBR2 regulates BRCA1 transcription is of particular interest. Although our current data do not support such a hypothesis, 8 another study showed that NBR2 knockdown modestly downregulated BRCA1 mRNA level. 10 Since these studies were conducted in different cell lines with different knockdown efficiencies, it is possible that NBR2 regulation of BRCA1 expression is context dependent, and it will be important to further clarify this question in future studies.…”
contrasting
confidence: 55%
See 3 more Smart Citations
“…Since many lncRNAs function to regulate the transcription of neighboring genes, the hypothesis that NBR2 regulates BRCA1 transcription is of particular interest. Although our current data do not support such a hypothesis, 8 another study showed that NBR2 knockdown modestly downregulated BRCA1 mRNA level. 10 Since these studies were conducted in different cell lines with different knockdown efficiencies, it is possible that NBR2 regulation of BRCA1 expression is context dependent, and it will be important to further clarify this question in future studies.…”
contrasting
confidence: 55%
“…Whether the NBR2-AMPK regulation discovered in our study can be applied to other lncRNAs that may regulate kinase function also awaits further investigation. In addition, our data show that NBR2 overexpression still partially inhibited tumor cell proliferation in AMPK-deficient cells, 8 suggesting the existence of AMPK-dependent and -independent mechanisms that mediate NBR2 function in tumor suppression. Since many lncRNAs function to regulate the transcription of neighboring genes, the hypothesis that NBR2 regulates BRCA1 transcription is of particular interest.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Additionally, lncRNAs can regulate kinase functions. LncRNA NBR2 engages a metabolic checkpoint by regulating AMP-www.impactjournals.com/oncotarget activated protein kinase (AMPK) under energy stress [10]. Accumulating evidence suggests that lncRNAs play a role in fundamental biological functions, and dysregulation of lncRNAs contributes to cancer development, progression, and metastasis in many malignancies [11].…”
Section: Introductionmentioning
confidence: 99%